The 2017 ISO New England System Operational Analysis and Renewable Energy Integration Study (SOARES) - Aramazd Muzhikyan; Steffi O. Muhanji; Galen D. Moynihan; Dakota J. Thompson; Zachary M. Berzolla; Amro M. Farid (Energy Reports, 2019)
The bulk electric power system in New England is fundamentally changing. The representation of nuclear, coal and oil generation facilities is set to dramatically fall, and natural gas, wind and solar facilities will come to fill their place. The introduction of variable energy resources (VERs) like solar and wind, however, necessitates fundamental changes in the power grid's dynamic operation. VER forecasts are uncertain, and their profiles are intermittent; thus requiring greater quantities of operating reserves. This paper describes the methodology and the key findings of the 2017 ISO New England System Operational Analysis and Renewable Energy Integration Study (SOARES). This study was commissioned by the ISO New England stakeholders to investigate the effect of several scenarios of varying generation mix on normal operating reserves. The project was conducted using the holistic assessment approach called the Electric Power Enterprise Control System (EPECS) simulator. The study finds a minimal impact on current normal operating conditions in the ISO-NE system for scenarios with relatively low penetration of VERs. Nevertheless, for scenarios with a significant presence of VERs, the system may require additional amounts of both upward and downward load following reserves and upward and downward ramping reserves to effectively maintain reliable operations. In these scenarios, the curtailment of semi-dispatchable resources also becomes an integral part of balancing performance; in part to complement operating reserves and in part to mitigate the topological limitations of the system. Indeed, the integration of significant amounts of VERs in relatively remote regions significantly increases the potential of congestion on several key interfaces. In many of these scenarios, the system experiences heavy saturations of regulation reserves and their increase would enhance the response to residual imbalances. The concludes with final insights into the emerging roles of curtailment, energy storage, and demand response as integral parts of normal balancing performance.
Keywords: 330; Economic dispatch; Enterprise control; ISO New England; Operating reserves; Renewable energy integration; Unit commitment